2020
DOI: 10.1093/jxb/eraa015
|View full text |Cite
|
Sign up to set email alerts
|

The mirid bug Apolygus lucorum deploys a glutathione peroxidase as a candidate effector to enhance plant susceptibility

Abstract: The mirid bug Apolygus lucorum has become a major agricultural pest since the large-scale cultivation of Bt-cotton. It was assumed that A. lucorum, similarly to other phloem sap insects, could secrete saliva that contains effector proteins into plant interfaces to perturb host cellular processes during feeding. However, the secreted effectors of A. lucorum are still uncharacterized and unstudied. In this study, 1878 putative secreted proteins were identified from the transcriptome of A. lucorum, which either h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 45 publications
2
44
0
Order By: Relevance
“…These substances may positively 11–17 or negatively 3, 18, 19 regulate insect performance on plant hosts. For example, salivary effectors such as Armet, Mp1, Mp2, Me47, Bt56, Bsp9, migration inhibitory factor, ferritin glutathione peroxidase and others impair plant defense responses 2, 3, 11, 12, 14, 17, 20–22 …”
Section: Introductionmentioning
confidence: 99%
“…These substances may positively 11–17 or negatively 3, 18, 19 regulate insect performance on plant hosts. For example, salivary effectors such as Armet, Mp1, Mp2, Me47, Bt56, Bsp9, migration inhibitory factor, ferritin glutathione peroxidase and others impair plant defense responses 2, 3, 11, 12, 14, 17, 20–22 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cell death and alteration in the hormone pathways of transfected plants may be positively correlated with ROS burst [ 20 ]. Although the five proteins are found to induce plant defenses, there may be other salivary components that suppress these detrimental effects, such as macrophage migration inhibitory factor in M. percicae , [ 25 ] and Al6 in Apolygus lucorum [ 27 ]. Further studies are warranted to unveil the complex mechanisms of R. pedestris saliva in insect–plant interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, salivary DNase II assists in the colonization of planthopper on host plants by degrading DAMPs released from damaged cells [ 26 ]. Recently, mirid bug was found to secrete a glutathione peroxidase that eliminates ROS accumulation and inhibits the pattern-triggered, immunity-induced cell death [ 27 ]. Such result indicates that salivary proteins are also important for true bugs.…”
Section: Introductionmentioning
confidence: 99%
“…Still, the studies paid main attention to digestive enzymes again, whereas very few discussed the effector functions of the salivary proteins. However, a recent study found that a glutathione peroxidase was highly expressed in the salivary glands of A. lucorum, who probably use it to eliminate the reactive oxygen species (ROS) accumulation in plants (Dong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%